Infrared spectroscopic measurements of the structure of organic thin films; furfural on Pd(111) and Au(111) surfaces. Issue 25 (14th June 2021) - Bavisotto, Robert; Hopper, Nicholas; Boscoboinik, Alejandro; Owen, Quintus; Tysoe, Wilfred T.
Abstract : This work demonstrates the use of reflection–adsorption infrared spectroscopy for continually monitoring the structure of organic thin films as a function of thickness and temperature to complement diffraction methods. Abstract : Electron and X-ray diffraction (XRD) and electron microscopy are predominantly used to investigate the structures of thin organic films deposited from the vapor at low temperatures on planar substrates to obtain the crystal structure of the thin film. This work illustrates how the structure of films on metal substrates can be continually monitored both during growth and as they are annealed until the film desorbs using reflection–absorption infrared spectroscopy (RAIRS). The chemical nature of the film, including molecular conformations, can be determined from the vibrational frequencies of the organic film, and the film orientation can be obtained using the infrared selection rules for reflective surfaces, which states that only those vibrational modes with a vibrational component perpendicular to the surface are detected. The approach is illustrated for furfural adsorbed on an unreactive metal, gold, and a more reactive one, palladium, to gauge the effect of substrate reactivity on the film structure. Furfural is chosen as a test molecule because it is planar, has two conformations depending on the orientation of the aldehyde group relative to the furyl ring, and the film structure has been studied by XRD. It is found that only the structure of the first layer in contact with the surface is influenced by the nature of the substrate. Changes in the ratio of the cis and trans conformation as well as changes in the degree of order of the furfural film are found as a function of film thickness and temperature.